2021
DOI: 10.1038/s41598-021-03717-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mothers’ nighttime responses on the sleep–wake rhythm of 1-month-old infants

Abstract: The purpose of this study was to analyze the influence of the mothers’ nighttime responses on the sleep–wake rhythm of their 1-month-old infants. This study used an anonymous self-administered survey questionnaire with 1133 mothers of 1-month-old infants. The questionnaire investigated basic information about the parents, growth environment of infants, mothers’ sleep patterns during pregnancy, and infants’ sleep patterns at the age of one month. Logistic regression analysis was used to analyze the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Berdasarkan penelitian yang telah dipublikasikan, pijat bayi bermanfaat untuk mempererat ikatan antara pemijat dengan bayi, meningkatkan durasi tidur bayi, serta mengurangi kejadian terbangun dari pertengahan tidur pada bayi (Kuroda et al, 2021). Selain penelitian tersebut, terdapat juga manfaat dari pijat bayi yaitu untuk mengasah kebiasaan pada bayi dan menstimulasi taktil sehinga pijat bayi juga membantu dalam perkembangan bayi secara keseluruhan (Priyadarshi et al, 2022).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang telah dipublikasikan, pijat bayi bermanfaat untuk mempererat ikatan antara pemijat dengan bayi, meningkatkan durasi tidur bayi, serta mengurangi kejadian terbangun dari pertengahan tidur pada bayi (Kuroda et al, 2021). Selain penelitian tersebut, terdapat juga manfaat dari pijat bayi yaitu untuk mengasah kebiasaan pada bayi dan menstimulasi taktil sehinga pijat bayi juga membantu dalam perkembangan bayi secara keseluruhan (Priyadarshi et al, 2022).…”
Section: Pendahuluanunclassified
“…Even at 1-month postpartum, parental involvement in infant sleep can influence sleep patterns. Immediately picking up 1-month-old infants when they cry at night results in longer sleep during the day, compared with delaying picking them up, 15 and affects the stability of infant sleep 16 . For infants to self-soothe and fall asleep independently, around 2–4 months of age, parents should start feeding or rocking them and then laying them down in the crib whilst drowsy but awake 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the effects of breathing problems during sleep in the perinatal period reported that conditions such as gestational hypertension, preeclampsia, and low birth weight infant delivery were more likely to occur in the presence of apnea [8]. Additionally, it is known that mothers' nighttime responses can affect the sleep-wake rhythm of 1-month-old infants [9].…”
Section: Introductionmentioning
confidence: 99%